2019
DOI: 10.1002/acm2.12612
|View full text |Cite
|
Sign up to set email alerts
|

Nonrigid registration of medical image based on adaptive local structure tensor and normalized mutual information

Abstract: Nonrigid registration of medical images is especially critical in clinical treatment. Mutual information is a popular similarity measure for medical image registration; however, only the intensity statistical characteristics of the global consistency of image are considered in MI, and the spatial information is ignored. In this paper, a novel intensity‐based similarity measure combining normalized mutual information with spatial information for nonrigid medical image registration is proposed. The different par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Gradient normalized mutual information function of B-ultrasound algorithm. [6][7] In this paper, a gradient normalized mutual information function ( )…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradient normalized mutual information function of B-ultrasound algorithm. [6][7] In this paper, a gradient normalized mutual information function ( )…”
Section: Methodsmentioning
confidence: 99%
“…Gradient normalized mutual information function of B-ultrasound algorithm. 6 - 7 In this paper, a gradient normalized mutual information function ( I GNMI ) is constructed as a similarity measure to increase registration accuracy and stability. Let the reference image and the image to be registered in this paper be A, B, and the normalized mutual information of A and B is…”
Section: Methodsmentioning
confidence: 99%
“…NMI is a concept whose properties have been studied in several ways and has been used for medical image registration problems 41 . Compared with mutual information, it is easy to compare the correlation between X and Y with normalized mutual information.…”
Section: Nmiedamentioning
confidence: 99%
“…To estimate the best parameters of rigid transformation for an optimal registration and to solve an ill-posed problem due to sparse information on intra- and inter-correspondence of scenes in multiple images, the mutual information (MI) criterium, which takes intensity information into account, is a valuable solution [ 18 , 19 , 20 ]. MI is a measure of common information in source and target images.…”
Section: Introductionmentioning
confidence: 99%
“…The results have indicated that the image registration becomes stable. Yang et al [ 20 ] proposed a new method that combines the normalized mutual information with spatial information for nonrigid medical image registration. The algorithm was validated on a simulated brain image with single-modality and multi-modality.…”
Section: Introductionmentioning
confidence: 99%